¿Es efectivo el entrenamiento en Neurofeedback para el tratamiento del TDAH ? Resultados a partir de una revisión sistemática (2014)
ABSTRACT: Based on a systematic review of empirical articles published between 2001 and 2011, this study aims to establish the viability of using Neurofeedback training as a technique to reduce the symptoms of attention deficit hyperactivity disorder in children and teenager. 88 articles were identified and based on the defined inclusion criteria, and 11 articles were selected. Evaluation of efficacy was based on the criteria defined by the Association of Applied Psychophysiology and Biofeedback (Association for Applied Psychophysiology and Biofeedback - AAPB -). The results point to a level of efficacy located between level two (potential effectiveness) and level three (probable effectiveness), therefore, it is necessary to conduct a research with a higher level of control of variables and larger samples. Related clinical uses and methodological aspects are discussed for future studies.